Chapter 12 Partiality for Humanity and Enhancement - Pugh, Jonathan (Oxford University Press, 2016)
We consider a strategy for justifying bio-conservative opposition to enhancement according to which we should resist radical departures from human nature, not because human nature possesses any intrinsic value, but because it is our nature. The idea is that we can be partial to humanity in the same way that common sense morality allows us to be partial to self, family, lovers, friends or our country. Whilst a similar idea was suggested by Bernard Williams and Jerry Cohen, it was not fully developed, and their arguments fail to mount a serious challenge to many forms of enhancement. We explore a better approach, drawing on recent literature about the nature and grounds of partiality, and attempt to elucidate what partiality for humanity might plausibly involve. We argue, however, that even if such partiality for humanity is defensible, it can at most only set limits on enhancement.